Help-seeking behaviors among survivors of intimate partner violence during pregnancy in 54 low- and middle-income countries: evidence from demographic and health survey data - Stiller, Mariella; Wilson, Michael; Bärnighausen, Till; Adedimeji, Adebola; Lewis, Erin; Abio, Anne (BMC public health, 2025)
Intimate partner violence (IPV) during pregnancy is a global issue of public health importance. Due to the low rates of help-seeking in response to IPV, research on survivors’ help-seeking behaviors is scarce, particularly within low- and middle-income countries (LMICs). The present study provides a cross-national evidence of informal and formal help-seeking patterns among pregnant women experiencing IPV.